Describing Student Activeness Using Transcript Based Lesson Analysis In Lesson Study Material Hydrostatic Pressure And Pascal's Law - Masniari, Deborah; Susanti, Nova; Lestari, Neneng; Gustria, Azfin (DIDAKTIKA, 2023)
This research was conducted to describe the activities of students using Transcript Based Lesson Analysis in Lesson Study on hydrostatic pressure and Pascal's Law class XI at SMAN 11 Muaro Jambi. This type of research was obtained from the results of learning video recordings, observer field notes and documentation. This research was carried out in collaboration with the observer team in each cycle through 3 lesson study stages, namely plan, do, and see. The analysis in this study cannot be carried out directly during learning but through the results of recording all teacher and student activities as well as observations made by the observer. Through this analysis one can see how the application of lesson study based on TCL or SCL in the learning process is TCL or SCL in nature from the many dialogues that arise between the teacher and students, this dialogue in the implementation of cycles I and II is shown in the number of words graph. Based on the results of this study, in cycle I it was seen that the teacher still dominated learning, not many students responded and answered questions given by the teacher. Cycle II in this study learning took place in group discussions where teacher dominance was still visible but better than cycle I because more student responses appeared and some students were active in discussing problem solving. Overall learning in class XI MIPA 2 SMAN 11 Muaro Jambi is categorized as TCL so that the suggestions contained in this study are for teachers to be able to study and design better learning so that they can realize learning that is student centered learning and apply learning with lesson study based on Transcript Based Lesson Analysis